Nice guys finish last: Emotional Leaders and Political action in Selected Íslendingasogur - Barreiro, Santiago Francisco; del Valle, Julián Juan Martín
The Íslendingasögur -the sagas about early Icelanders- are texts composed mostly during the thirteenth and fourteenth centuries that depict, among other things, a series of prominent men as exemplary moral figures and highly honourable individuals that, nevertheless, fail in their leadership aims. Our basic hypothesis informing this chapter is that the mentioned traits ascribed to them are intimately entwined as an effect of the political realism?sometimes bordering on cynical realpolitik? which permeates the genre. We aim to verify the said hypothesis through an analysis of three such figures: Þórólfr Kveld-Úlfsson from Egils saga Skalla-Grímssonar, Arnkell goði from Eyrbyggja saga, and Blund-Ketill from H?nsa-Þóris saga. Our aim is to assess whether there is a link between political achievements and pragmatic, rational actions in the sagas by examining the opposite situation: we intend to consider whether political failure can sometimes be driven by emotional reactions in the contexts in which pragmatic answers to problems are expected. Fil: Barreiro, Santiago Francisco. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Saavedra 15. Instituto Multidisciplinario de Historia y Ciencias Humanas; Argentina Fil: del Valle, Julián Juan Martín. No especifíca;